2006
DOI: 10.1118/1.2201149
|View full text |Cite
|
Sign up to set email alerts
|

Properties of unflattened photon beams shaped by a multileaf collimator

Abstract: Several studies have shown that removal of the flattening filter from the treatment head of a clinical accelerator increases the dose rate and changes the lateral profile in radiation therapy with photons. However, the multileaf collimator (MLC) used to shape the field was not taken into consideration in these studies. We therefore investigated the effect of the MLC on flattened and unflattened beams. To do this, we performed measurements on a Varian Clinac 21EX and MCNPX Monte Carlo simulations to analyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
155
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 13 publications
5
155
0
1
Order By: Relevance
“…The curves are normalized to 100% on the central axis. Since only FFF modes were commissioned for the Edge, we could not use the penumbra normalization method proposed by Pönisch et al (34) Figure 5 shows direct comparison of profile curves between the Edge and the TrueBeam for two representative fields using 10X FFF: 2×2 cm2 and 10×10 cm2. The profiles between the Edge and the TrueBeam were practically the same, with slightly sharper penumbra obtained on the Edge at all the depths.…”
Section: Resultsmentioning
confidence: 99%
“…The curves are normalized to 100% on the central axis. Since only FFF modes were commissioned for the Edge, we could not use the penumbra normalization method proposed by Pönisch et al (34) Figure 5 shows direct comparison of profile curves between the Edge and the TrueBeam for two representative fields using 10X FFF: 2×2 cm2 and 10×10 cm2. The profiles between the Edge and the TrueBeam were practically the same, with slightly sharper penumbra obtained on the Edge at all the depths.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the MLC transmission and dosimetric leaf gap for 6 MV FFF beam were 1% and 1.1 mm as compared to 1.5% and 2 mm for 6 MV flat beam, respectively. Moreover, the comparison of penumbra of 6 MV flat beam with 6 MV FFF beam for MMLC in Table 8 revealed the softer photon beam spectrum and missing scatter from flattening filter resulting in a smaller penumbra in 6 MV FFF beam (22) . All the above parameters (MLC transmission, dosimetric leaf gap, lower energy spectra, and penumbra) had a positive impact on reducing the normalV20Gy, normalV13.5Gy, normalV12.5Gy, and normalV5Gy with 6 MV FFF beam.…”
Section: Discussionmentioning
confidence: 93%
“…Various studies have reported the characteristics of FFF beams based on measurements 1 , 2 , 3 and Monte Carlo simulation 4 , 5 from Varian linacs. The properties of FFF beams have also been summarized for Elekta 6 , 7 , 8 , 9 and Siemens (10) linacs.…”
Section: Introductionmentioning
confidence: 99%
“…The removal of the flattening filter alone, without any further modifications in the beam control parameters, results in a higher dose rate and reduced beam quality 1 , 2 , 3 , 6 , 7 , 11 , 12 . The beam quality can be increased to that of the corresponding flattened beam by matching the percentage depth dose (PDD) at 10 cm depth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation